Different types of plastic bioremediation using soil bacteria and Superworm zophobas morio larvae - Zaman, Ifthikhar; Al Shahariar, Mahruf; Howlader Emu, MD. Rezanur Rahman (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2022.